Switching monopolar radiofrequency ablation improves long-term outcomes of medium-sized hepatocellular carcinoma - Lin, Chen-Chun; Lui, Kar-Wai; Chen, Wei-Ting; Hsieh, Yi-Chung; Cheng, Ya-Ting; Teng, Wei; Lin, Shi-Ming (European radiology, 2021)
Objectives Radiofrequency ablation (RFA) of medium-sized (3–5 cm) hepatocellular carcinoma (HCC) is suboptimal. Switching monopolar RFA (SW-RFA) enlarges the ablative volume to better cover larger tumors. This study aims to compare the long-term outcomes of medium-sized HCC treated by either SW-RFA or single-monopolar RFA (S-RFA). Methods We retrospectively reviewed 139 cases (147 medium-size HCC) between 2008 and 2014. Under propensity score matching, a total of 43 paired patients with medium-size HCC and balanced clinical variables treated by either SW-RFA or S-RFA were selected for comparison. Results SW-RFA showed a higher rate of achieving an adequate safety margin ( p = 0.002). After a mean follow-up period of 40.4 months, SW-RFA produced significantly lower global RFA failure rates ( p < 0.001) and better overall survival ( p = 0.005) compared to S-RFA. SW-RFA was independently associated with a decreased risk of global RFA failure (hazard ratio [HR]: 0.136, 95% confidence interval [CI]: 0.030–0.607, p = 0.009) and improved overall survival (HR: 0.337, 95% CI: 0.152–0.747, p = 0.007). By last follow-up, the SW-RFA group maintained a superior tumor-free rate ( p = 0.010) and fewer progressions to Barcelona Clinic Liver Cancer stage C ( p = 0.011). Major complication rates were comparable in both groups (SW-RFA: 2.3% vs. S-RFA: 4.7%, p = 1.000). Conclusions The switching multi-monopolar ablation technique could be beneficial for patients with medium-sized HCCs given sustained control of larger tumors with better overall survival. Key Points • Switching monopolar ablation could provide a sustained local tumor control and better overall survival than single-monopolar ablation for the medium-sized hepatocellular carcinoma. • Compared to single-monopolar ablation, switching monopolar ablation could create a larger homogeneous coagulation volume by using a shorter total ablation time to achieve a higher rate of adequate safety margin for a medium-sized HCC. • Patients with medium-sized HCC can be maintained at a higher rate of tumor-free status and at a lower risk of progression into BCLC stage C in the follow-up period after ablation by switching monopolar than by single-monopolar ablation.